2008
DOI: 10.1016/j.pep.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and characterization of recombinant mouse translation initiation factor eIF4E as a dihydrofolate reductase (DHFR) fusion protein

Abstract: One of the earliest steps in translation initiation is recognition of the mRNA cap structure (m7GpppX) by the initiation factor eIF4E. Studies of interactions between purified eIF4E and its binding partners provide important information for understanding mechanisms underlying translational control in normal and cancer cells. Numerous impediments of the available methods used for eIF4E purification led us to develop a novel methodology for obtaining fractions of eIF4E free from undesired byproducts. Herein we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We therefore analyzed eIF4E binding to RNAs with different first nucleotides. Most previous studies of eIF4E binding affinity used cap analogs such as m7GTP or m7GpppG and reported Kd values ranging from low μM to few nM ( Ueda et al, 1991 ; Carberry et al, 1992 ; Minich et al, 1994 ; Sha et al, 1995 ; Hagedorn et al, 1997 ; Miyoshi et al, 1999 ; Wieczorek et al, 1999 ; Hsu et al, 2000 ; von Der Haar et al, 2000 ; Niedzwiecka et al, 2002 ; Scheper et al, 2002 ; Ghosh et al, 2008 ; Thillier et al, 2012 ). We chemically synthesized three capped RNA oligos as previously described ( Lavergne et al, 2008 ; Thillier et al, 2012 ), 10 nt long each that differ in their first nucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore analyzed eIF4E binding to RNAs with different first nucleotides. Most previous studies of eIF4E binding affinity used cap analogs such as m7GTP or m7GpppG and reported Kd values ranging from low μM to few nM ( Ueda et al, 1991 ; Carberry et al, 1992 ; Minich et al, 1994 ; Sha et al, 1995 ; Hagedorn et al, 1997 ; Miyoshi et al, 1999 ; Wieczorek et al, 1999 ; Hsu et al, 2000 ; von Der Haar et al, 2000 ; Niedzwiecka et al, 2002 ; Scheper et al, 2002 ; Ghosh et al, 2008 ; Thillier et al, 2012 ). We chemically synthesized three capped RNA oligos as previously described ( Lavergne et al, 2008 ; Thillier et al, 2012 ), 10 nt long each that differ in their first nucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…[26] This cap-free eIF4E had the advantage of avoiding the contamination of eIF4E purified from cap-affinity chromatography with cap-analog[15]. Generally, DHFR-eIF4E was overexpressed as a fusion protein in BL21 DE3 E. coli cells.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin and streptavidin (Sigma-Aldrich) and rabbit polyclonal anti-DNP IgG (Invitrogen) were labeled with Alexa Fluor 488– or Alexa Fluor 555–succinimidyl ester (Invitrogen) as per the manufacturer’s instructions. E. coli DHFR, expressed from a plasmid constructed by inserting the complete coding sequence of the protein between the NdeI and BamHI sites of pMAL-p4X (New England Biolabs, Inc.), was purified from E. coli by affinity chromatography on methotrexate-Sepharose ( Ghosh et al, 2008 ) and labeled with Alexa Fluor 555–succinimidyl ester. Fluorescein-labeled folate was originally obtained as a gift from S. Mayor (National Centre for Biological Sciences, Bangalore, India) and later synthesized by the method of McAlinden et al (1991) , as was its rhodamine-labeled analogue.…”
Section: Methodsmentioning
confidence: 99%